Demand Elasticities for Mobile Telecommunications in Austria - Ralf Dewenter; Justus Haucap (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
This paper analyses price elasticities in the Austrian market for mobile telecommunications services using data on firm specific tariffs in the period between January 1998 and March 2002. Dynamic panel data regressions are used to estimate short-run and long-run demand elasticities for business customers and for private consumers with both postpaid contracts and prepaid cards.We find that business customers have a higher elasticity of demand than private consumers, where postpaid customers tend to have a higher demand elasticity than prepaid customers. Also demand is generally more elastic in the long run. In addition, the paper also provides estimates for firm-specific demand elasticities which range from -0.47 to -1.1.
Keywords: C23; L13; L96; 330; Mobile telephony; price elasticities; unbalanced panel data; dynamic panel data analysis; Mobilkommunikation; Preiselastizität; Schätzung; Österreich